Exploring the impact of virtual leadership on job satisfaction in the post-COVID-19 era: The mediating role of work–life balance and trust in leaders - Al Dilby, Hala Koleilat; Farmanesh, Panteha (Frontiers in Psychology, 2023)
Leadership remains a highly important role in the management of employees' psychological and physical well-being, particularly in the aftermath of the COVID-19 pandemic. As various sectors adapted virtual settings to overcome the restrictions posed by the pandemic, the vitality of virtual leaders became more pivotal as they could enhance the virtual work environment for employees and steer teams toward organizational goals. This study assessed the effect of virtual leaders on employees' job satisfaction in the information technology sector as a high-performance industry. Furthermore, the mediating effects of trust in leaders and work–life balance on the virtual leadership–job satisfaction relationship were assessed in the proposed model of this research. Through a deductive quantitative approach and using purposive and convenience sampling techniques, a total of 196 respondents participated in the research. The data analysis process was deployed via Smart PLS software and the PLS-SEM technique. The results showed that virtual leaders play a major role in determining information technology (IT) employees' job satisfaction while the mediating effects of both trust in leaders and work–life balance are significant factors that can enhance the work environment for leaders to achieve better results. The statistically significant findings of this research suggest a number of positive work outcomes and pathways with scholarly and managerial implications that can be beneficial for leaders in relevant sectors.